Methylation of wood fatty and resin acids for production of biodiesel - Demirbaş, Ayhan (ELSEVIER, 2011)
The purpose of the present paper is to evaluate the potentiality of the wood oil of Oriental spruce (Spruce orientalis) for biodiesel production. Two methods have been applied for obtained wood oil with and without solvent such as separation of crude tall oil from sulfate soaps by Kraft pulping process. Production of biodiesel from wood oil follows two steps, first extraction of oil using a solvent (acetone) and then base catalyzed (KOH) or non-catalytic supercritical methanol transesterification. This paper studied the effect of temperature on transesterification of wood oil to find the optimum temperature of maximum biodiesel yield. Transesterification of the wood oils were performed in a 100-mL cylindrical autoclave using supercritical methanol. In a typical run, the autoclave was charged with a given amount of the wood oil (20–25 g) and alcohol (20–50 g) with changed molar ratios at 500, 525, 550 and 575 K. The yield of the biodiesel produced under optimal condition is 96–98%.
Keywords: Biodiesel; Wood oil; Extractives; Fatty acids; Tall oil